PERTUMBUHAN DAN PRODUKSI JAGUNG PULUT LOKAL (Zea mays ceratina Kulesh) PADA BEBERAPA DOSIS PUPUK NPK - Juandi Tengah; Selvie Tumbelaka; Marjam M. Toding (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ The purpose of this study was (1) to know the growth and production of local waxy corn on various dosage of NPK fertilizer ; (2) to obtain the proper dosage of fertilizer in growth and production of local waxy corn. This study was conducted in Insil village, Passi Timur District, Bolaang Mongondow Regency with attitude 1100 meters above sea lever, from June to August 2016. Using a Randomized Block Design with five treatments of NPK fertilizer dosage which are P0 = 0 kg ha-1 of NPK fertilizerÂ (as a control), P1 = 200 kg ha-1 of NPK fertilizer, P2 = 300 kg ha-1 of NPK fertilizer, P3 = 400 kg ha-1 of NPK fertilizer, and P4 = 500 kg ha-1 of NPK fertilizer. The results showed that treatmen of NPK fertilizer dosage only had effected on plant height of local waxy corn but had no effected on length of cob, diameter of cob, fresh weight of with corn husk and fresh weight of cob without cornhusk. Keywords : Waxy corn, fertilizer, production